Patient with tetralogy of Fallot at 30-year follow-up – a historical overview of the treatment of the defect - Gruszczyńska, Anna; Kowalik, Krzysztof; Modrzejewski, Andrzej (Family Medicine & Primary Care Review, 2024)
The authors present the case of a patient with tetralogy of Fallot. The patient underwent surgery to correct the defect 30 years ago. Our patient remains in good condition, currently reporting only poorer exercise tolerance. The authors attempted to analyse the development of treatment methods for tetralogy of Fallot based on world literature with reference to the case described in this paper. This paper presents the history and advances that have been made in the treatment of Fallot syndrome. Numerous details and dates are cited regarding the history of the treatment of the defect. Due to the vastness of the subject of tetralogy of Fallot, the article does not discuss contemporary treatments for the defect.